The Challenges and Solutions of State Islamic Universities Post Remuneration Implementation - Yayu Putri Senjani (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2022)
Purpose: The remuneration is a working reward system applied to the BLU-Satker. 15 of 19 PTKIN-BLU have already implemented remuneration. This research aims to identify the challenges of PTKIN BLU after implementing remuneration. Methodology: The research method used a qualitative method descriptive by adding quantitative data analysis. UIN Sunan Kalijaga Yogyakarta and UIN Sultan Maulana Hasanuddin of Banten are the samples in this research. They are representative of PTKIN BLU in big size and small size. Findings: Managers and employees of BLU who became the informant in this study stated that PTKIN BLU has challenges. BLU income has not been optimal, and an unobjective and measurable performance assessment system and have differences of opinion among BLU managers. However, some efforts have been made by PTKIN BLU to succeed in the implementation of remuneration. They are the strengthening of the business unit, the addition of a postgraduate department, and establishing and developing an adequate performance assessment system. Novelty: This study identifies in more detail what challenges are faced when remuneration is applied so that it can affect the performance of employees and organizations. In addition, this study also identified the efforts of BLU managers to overcome these challenges and obstacles. Keywords: Remuneration, Public Service Agency (BLU), Performance.